PENGARUH VOLUNTARY DISCLOSURE, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KUALITAS LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Rumapea, Melanthon; Hutabarat, Chiristian Veri; Goh, Thomas Sumarsan; Simanjuntak, Gracesiela Yosephine (Journal Accounting International Mount Hope, 2024)
The aim of this research is to examine the influence of Voluntary Disclosure, Managerial Ownership and Institutional Ownership partially and simultaneously on Earnings Quality. The population in this study is 28 Coal Sector Mining Companies listed on the Indonesia Stock Exchange. The sample used in this research was 20 companies. The observation year for this research is 3 years starting from 2019 to 2021. The data in this research was obtained from www.idx.co.id. This research uses quantitative methods and uses the SPSS application for data processing in research. The results obtained from this research are that partially Voluntary Disclosure and Institutional Ownership do not have a significant effect, while Managerial Ownership has a significant effect on Earnings Quality. Simultaneously, Voluntary Disclosure, Managerial Ownership and Institutional Ownership have a significant effect on Earnings Quality.